Gain enhancement of circular waveguide antennas using near-zero index metamaterials - Mohammadi, E.; K. L. Tsakmakidis; Sohrabi, F.; Tavakoli, A.; Dehkhoda, P. (Microwave and Optical Technology Letters, 2019)
In this article, a rigorous analytical methodology is introduced for designing near-zero refractive index metamaterials (NZIMs). Our proposed NZIM media is realized by three stacked layers of perforated metallic surfaces, each layer composed of a fishnet-like periodic array of square holes. By a proper design of such structures, a low refractive index medium is achieved at their corresponding plasma frequency. The low refractive index property is studied by retrieving the effective parameters of NZIM via inversion techniques, which gives an effective near-zero refractive index, at an operating frequency of 1.5 GHz. Then, the designed NZIM is used for gain enhancement of a circular waveguide antenna. The analysis shows that the proposed platform can enhance the directivity of our antenna by 3 dB while maintaining the return loss <−20 dB. © 2019 Wiley Periodicals, Inc.
cited By 0